Differences in temporal order memory among young, middle-aged, and older adults may depend on the level of interference - Rotblatt, Lindsay J.; Sumida, Catherine A.; Van Etten, Emily J.; Turk, Eva Pirogovsky; Tolentino, Jerlyn C.; Gilbert, Paul E. (Frontiers in Aging Neuroscience, 2015)
Age-related changes in temporal order memory have been well documented in older adults; however, little is known about this ability during middle age. We tested healthy young, middle-aged, and older adults on a previously published visuospatial temporal order memory test involving high and low interference conditions. When interference was low, young and middle-aged adults did not differ, but both groups significantly outperformed older adults. However, when interference was high, significant differences were found among all three age groups. The data provide evidence that temporal order memory may begin to decline in middle age, particularly when temporal interference is high.